Studies of Aβ aggregation, toxicity and cellular uptake - Beretta, Chiara (2016)
Alzheimer’s disease (AD) is the most common type of dementia observed in the elderly. The symptoms of the disease are provoked by neuronal loss caused by neurofibrillary tangles and amyloid plaques. The molecular processes that underlie AD’s pathology are at this day not well understood. Amyloid β peptide (Aβ) appears to be one of the causes of neuronal toxicity. 42-residue Aβ (Aβ42) forms insoluble oligomers and fibrils which seem to be one of the leading causes of AD. To study the different molecular processes behind aggregation, toxicity and cellular uptake of Aβ42, monomer purification and labeling with a fluorescent dye are crucial. More successful fluorescent labeling without disrupting the structure and aggregation of Aβ, would increase accuracy and reliability of a wide variety of cellular studies. This study aims to improve the protocol for monomer purification and labeling. Aβ with an introduced Cys for labeling (Aβ MC1-42) was labeled with ATTO Oxa11 (ATTO-TEC) dye to a degree of labeling between 11 and 13%. Different conditions were explored and the labeling was most successful with 7 M guanidinium hydrochloride buffer, pH 8 and an incubation time of 3 hours. The labeled Aβ (MC1-42), that had been purified under sterile conditions, was added to HEK 293 cells at three different concentrations and studied under the confocal microscope. Aβ is visible in the cells, which suggests that the peptide was internalized and/or interacting with the plasma membrane. Thioflavin T (ThT) and pentameric formyl thiophene acetic acid (pFTAA) assays were performed to study the aggregation kinetics of labeled Aβ (MC1-42) compared to wild-type Aβ42 and unlabeled Aβ (MC1-42). The assays showed a lower fibrillation rate for Aβ (MC1-42), both labeled and unlabeled. The ThT assay showed that addition of dye seemed to give a slightly lower fibrillation rate, which could mean that the dye interferes with the assay. The pFTAA assay didn’t show any signal for Aβ (MC1-42), and needs therefore to be rerun with more controls before any conclusion could be drawn. A preliminary experiment was carried out, in which labeled Aβ42 at a concentration of 2.1 μM was added to human CHME3 microglial cells and studied under the confocal microscope. Aβ seemed to be internalized by the cells. These findings provide a promising point of entry for further research on Aβ42 labeling techniques and cellular studies.